2017
DOI: 10.17221/480/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Boron availability and uptake under increasing phosphorus rates in a pot experiment

Abstract: The boron (B) availability in soils, B uptake and possible B interactions with phosphorus (P) were studied in a pot experiment with increasing P rates. Three soil types of different characteristics were used for the experiment that lasted two years. The two soil tests were used in the experiment – Mehlich 3 and NH<sub>4</sub>-acetate. Significant positive correlations were found between barley dry matter yield, B content in plants and B uptake under increasing P treatments (P ≤ 0.001). The signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The enhanced B contents in wheat plants in relation to increasing P levels also suggested the improvement of metabolic functioning of plants. Muhlbachova et al (2017) have found positive correlation between dry matter yield and B contents in Barley (R 2 = 0.3273, p ≤ 0.001) under P fertilization. In contrast (Kaya et al, 2009) reported that B toxicity in tomato plants could be mitigated by the supplemental P fertilizer.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The enhanced B contents in wheat plants in relation to increasing P levels also suggested the improvement of metabolic functioning of plants. Muhlbachova et al (2017) have found positive correlation between dry matter yield and B contents in Barley (R 2 = 0.3273, p ≤ 0.001) under P fertilization. In contrast (Kaya et al, 2009) reported that B toxicity in tomato plants could be mitigated by the supplemental P fertilizer.…”
Section: Discussionmentioning
confidence: 77%
“…Plant biomass production can be predicted by the available P and B contents, as stated by Davies et al (2011). Several earlier investigations revealed that combined application of P and B significantly enhanced the growth, yield and quality of various field crops (Huang et al, 2012;Kabir et al, 2013;Chowdhury et al, 2015;Muhlbachova et al, 2017). Therefore, an adequate and consistent supply of P and B is necessary to achieve better nutrient balances and more biomass production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation